A CRET‐Based Multicolor Sensing Nanoplatform for Simultaneously and Sensitively Visualizing Multiple Circulating MicroRNAs. Issue 3 (1st August 2021) - Xu, Jie; Shi, Lin; Wang, Han; Li, Tao
Abstract: Invited for this month's cover is the group of Prof. Tao Li at the University of Science and Technology of China. The cover picture shows the imaging strategy of multicolor chemiluminescence sensing platform for multiple miRNA sensing, which employs a smartphone as the detector. More information can be found in the 10.1002/anse.202100012 . Abstract : "A CRET‐based multicolor smartphone sensing nanoplatform integrating chemiluminescence imaging arrays for simultaneous and sensitive detection of multiple miRNAs was constructed. SNAzyme with high catalytic activity for CL and CTET reaction is produced in the presence of target miRNAs. The nanoplatform can simultaneously visualize multiple miRNAs related to acute myocardial infarction with high sensitivity and selectivity in patient serum, and directly detect endogenous miRNAs in human serum." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/anse.202100012 ).